GAMBARAN PERILAKU BERDASARKAN SOSIODEMOGRAFI, PENGETAHUAN, PERSEPSI TERKAIT ORAL HYGIENE PADA MAHASISWA KESEHATAN DAN NON KESEHATAN UNIVERSITAS UDAYANA - Made Laras Fatmala Eni; Sari Kusumadewi; Komang Ayu Kartika Sari (ODONTO : Dental Journal, 2018)
Background: The number of dental and oral diseases 24% cases occur in the age of 18 years which is the age of the college students. At this age, college students are expected to have better knowledge and behavior in maintaining oral health. This study was to describe the behaviour based on sociodemography, knowledge and perceptions related to oral hygiene in medical and non medical students of Udayana University.Method: This study use a quantitative descriptive study with cross-sectionalapproach. The total samples were 100 participants. Data were collected using questionnaire to determine the level of knowledge, perceived, behaviour, and oral hygiene.Result: The results showed that, good behaviour in maintaining dental and oral health was 47 respondents (94%) in Dentistry students and 14 respondents (28%) in English Literature’s students.Conclusion: The proportion of Dentistry students with good behavior wasgreater in those aged ≥21 years, women, high knowledge, perceived as notvulnerable, not serious, had no benefts, no barrier, feel capable and havehigh cues to action. The proportion in English literature with good behaviourwas greater in those <21 years old, women, high knowledge, perceived as not vulnerable, serious, benefcial, no barrier, feel capable and high cues to action.